Managing Resources to Build Back and Create a Better Future for Nias : Nias Public Expenditure Analysis - World Bank (Washington, DC, 2012)
Already one of the poorest regions in Indonesia, the island of Nias was badly affected by the twin disasters of the 26 December 2004 tsunami and a devastating earthquake that struck three months later, on 28 March 2005. Now, more than two years after the disasters and despite the significant progress that has undoubtedly been made, some troubling trends are starting to emerge, of which this report takes stock. In particular, funds are not being disbursed at the desired pace as the reconstruction effort faces enormous implementation challenges. The allocation of significant resources for reconstruction, as well as the decentralization process, entails both opportunities and challenges for the development of Nias. This report assists in making use of those opportunities and overcoming the challenges by informing the planning and budgeting process of the two district governments in Nias, and analyzing constraints in public financial management in both districts, as well as identifying key gaps in the reconstruction process.